Tube-in-tube endoscopic vacuum therapy for the closure of upper gastrointestinal fistulas, leaks, and perforations - Simas de Lima, Marcelo; Uemura, Ricardo Sato; Gusmon-Oliveira, Carla Cristina; Pombo, Amanda Aquino de Miranda; Martins, Bruno Costa; Lenz, Luciano; Kawaguti, Fabio Shiguehissa; De Paulo, Gustavo Andrade; Baba, Elisa Ryoka; Safatle-Ribeiro, Adriana V.; Ribeiro, Ulysses, Jr.; Monkemüller, Klaus; Maluf-Filho, Fauze (Endoscopy, 2022)
Background Although endoscopic vacuum therapy (EVT) has been successfully used to treat postoperative upper gastrointestinal (UGI) wall defects, its use demands special materials and several endoscopic treatment sessions. Herein, we propose a technical modification of EVT using a double tube (tube-in-tube drain) without polyurethane sponges for the drainage element. The tube-in-tube drainage device enables irrigation and application of suction. A flowchart for standardizing the management of postoperative UGI wall defects with this device is presented.Methods An EVT modification was made to achieve frequent fistula cleansing, with 3 % hydrogen peroxide rinsing, and the application of negative pressure. A tube-in-tube drain without polyurethane sponges can be inserted like a nasogastric tube or passed through a previously positioned surgical drain. This was a retrospective two-center observational study, with data collected from 30 consecutive patients. Technical success, clinical success, adverse events, time under therapy, interval time from procedure to fistula diagnosis and treatment start, size of transmural defect, volume of cavity, number of endoscopic treatment sessions, and mortality were reviewed.Results 30 patients with UGI wall defects were treated. The technical and clinical success rates were 100 % and 86.7 %, respectively. Three patients (10 %) had adverse events and three patients (10 %) died. The median time under therapy was of 19 days (range 1–70) and the median number of endoscopic sessions was 3 (range 1–9).Conclusions This standardized approach and EVT modification using a tube-in-tube drain, with frequent fistula cleansing, were successful and safe in a wide variety of UGI wall defects.